Peran Program Sore Ceria Bagi Pendengar Radio RRI Pro 2 Bukittinggi - Amelia, Silvia; Afandi, Yusuf; Hendra, Tomi; Ahmad, Fajri (STAI Bumi Silampari, 2024)
This study examines the role of the Sore Ceria Program on RRI PRO 2 Bukittinggi in attracting and retaining listeners through informative, educational, and entertaining content. Using qualitative methods with observation, interviews, and documentation, this study involved the Broadcast Coordinator and broadcasters of LPP RRI Pro 2 Bukittinggi as the main informants, as well as students and listeners as supporting informants. The results of the study indicate that the Sore Ceria Program plays an important role in providing information, education, and entertainment that not only increases insight but also overcomes listeners' boredom. Active interaction between broadcasters and listeners creates a pleasant atmosphere, while educational content provides real benefits, so that this program has succeeded in providing a positive impact in filling listeners' free time in the afternoon.